Bilateral Acute Angle Closure Glaucoma as a Presentation of Vogt-Koyanagi-Harada Syndrome in Four Chinese Patients: A Small Case Series. (August 2013) - Yao, Jing; Chen, Yuhong; Shao, Tingting; Ling, Zhihong; Wang, Wenji; Qian, Shaohong
<x xml:space="preserve">Abstract</x> Purpose: To report the clinical features of Vogt-Koyanagi-Harada syndrome presented with bilateral acute angle closure glaucoma in 4 Chinese patients. Methods: The medical records were retrospectively reviewed. Results: Visual acuity ranged from counting fingers before the eye to 6/30. Intraocular pressure ranged from 22.2 to 29.7 mmHg with or without anterior chamber inflammation. Mild vitritis and massive exudative retinal detachment were seen. B scan and fundus fluorescein angiography supported the diagnosis. After corticosteroid treatment, the increased intraocular pressure was resolved with deepened anterior chamber and open angle. Inflammation was controlled and visual acuity was improved. Conclusions: Bilateral acute angle closure glaucoma could be the initial symptom of Vogt-Koyanagi-Harada syndrome. Mild increased intraocular pressure in association with moderate to severe visual disturbance in both eyes is an important sign of this diagnosis. Careful fundus examination and B scan are helpful in diagnosis.